Новый вид рода Hoffmannina (Acariformes, Trombiculidae) из Киргизии - Гуща, Г.И.; Харадов, А.В. (Вестник зоологии, 1985)
Hoffmannina tshatkalica sp. n. is described upon larvae collected from Alticola argentata (Rodentia) in Sary-Tshelek Nature Reserve, Kirghiz SSR. From other species of the genus, known to occur in the USSR, it differs by characters of idiosomal and palpal chetotaxy, Ip value. Similar to Balkanian H. danieli Kolebinova and H. talpae Kolebinova and to Pyrenaic H. galla Kolebinova, differing from them by larger size (Ip>1000), number of genualae (ga), palpal and galeal cheta chetotaxy, more numerous NDV.